Utilization of Pseudomonas fluorescens as Antimicrobial agent on Lipolysis Inhibitition of Rice Bran - Widiyastuti, Titin; Prayitno, Caribu Hadi; Munasik, Munasik (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2002)
Feedstuff was limited by fat content, certainly, if the material feedstuff was storage on long time periods. Fat was oxidized or hydrolyzed, which was decreased nutritional quality. A Research on Inhibited ofÂ Lypolysis Rice Bran with anti-microbial compound of Pseudomonas fluorescens was conducted during ten month. The research used experiment methods, with Randomized Completely Block Design, storage as block and concentration of anti-mikrobial compound as treatment. Fat and polyunsaturated fatty acids content during storage was observed. Result of experiment showed anti-microbial compound inhibited oxidize and hydrolyze process of fat rice bran during six month storage. (Animal Production 4(2): 89-93 (2002)Â